Testing the Antihyperurisemic Effectiveness of the Ethanol Extract of Henna Leaf (Lawsonia Mermis L.) on Induced Male Mice (Mus Musculus) with Chicken Liver and Potassium Bromate - Muhammad Gunawan; Tanjung, Siti Aisyah; Safriana, Safriana; Fitriani, Enny (PT Inovasi Pratama Internasional, 2024)
Hyperuricemia is a condition that is marked by an increase in blood pressure in the blood that exceeds the normal level, ie above 7.0 mg/dl in the patient and above 6.0 mg/dl in women. It is generally intended to address hyperuricemia in the use of synthesized drugs that can give rise to the effect of retinal pain, vomiting, diarrhea, damage to the liver, nephritis in the brain and hypertheritivity. By therefore developing alternative treatments using plant medicine as well as parsley nails (Lawson mermis L.). This research is aimed at identifying extracurricular nephew nails (EEDPK) against decreasing levels of pregnancy in males who are induced by liver cancer and galleria. This research uses experimental methods with gathering and processing materials, identification of growth, making implicit, making extracts, determining water levels, preparing animal trials, and testing EEDPK effects. Animals used 24 eggs were divided into 6 groups of tests, group divisions included normal groups, induction, comparison, and EEDPK in 3 doses of 150 mg/kg body weight, 300 mg/kg body weight, and EEDPK 600 mg/kg body weight version 25 with 95% confidence level. The results of the EEDPK water level assessment were 3.33%. The results of the efficacy of hyperuricides will be shown that EEDPK provides the effect of the most effective extracts as antihyperuricemia is 300 mg/kgBB compared to other groups of extract.